Random lasers from the natural inverse photonic glass structure of Artemia eggshells. (21st July 2022) - Mai, Hanh Hong; Nguyen, Trong Tam; Nguyen, Tien Thinh; To, Thanh Thuy; Nguyen, Toan T; Choi, Youngwoon; Choi, Wonshik; Ta, Van Duong
Abstract: In this study, we demonstrate a simple approach to fabricate a high-performance random laser (RL) from the natural inverse photonic glass structure of Artemia eggshells. Herein, the three-dimensional structures of Artemia eggshells provide an ideal scattering medium with a significantly high-reflectance stopband which facilitates resonance feedback for random lasing action. By doping organic dye molecules into the Artemia eggshells, RLs are realized by optical pumping with a threshold of 79 μ J mm −2, and a quality ( Q ) factor of 2328. In comparison with other works on RLs from natural photonic crystals such as butterfly wings, our RLs demonstrate a significantly lower lasing threshold and a comparable Q factor. Our results indicate that the natural inverse photonic glass structure is not only served as an effective scattering medium for random lasing but also paves a novel approach in designing and fabricating bio-controlled photonic devices.